Odontogenic keratocyst with dentinoid formation - Ng, K.H.; Siar, C.H. (2003)
Although rare, hard tissue deposits, namely dystrophic calcifications and cartilage, have been reported to occur in the connective tissue wall of the odontogenic keratocyst. However, dentinoid formation has not been previously documented. A case involving the left mandibular premolar-molar region in a 37-year-old Malay male is described here along with a brief review on the reported prevalence of hard tissue deposits in the odontogenic keratocyst. Differential diagnosis of this case from other dentinoid-forming odontogenic Cysts and tumors-notably calcifying odontogenic cyst, odontoma, ameloblastic fibro-odontoma, central odontogenic fibroma and adenomatoid odontogenic tumor that may present with dentin/dentinoid formation-is discussed.